Infection transmission via mobile phones in a mass gathering setting: Public knowledge, attitudes and practices in Makkah city, Saudi Arabia - Mohamed O. Nour; Hatim A. Natto; Tassnym H. Sinky; Mashael S. Alfaifi; Mohammed Fayez J. Alharbi; Anoud Mateq Keshan Allahyani; Wed Abdulrahman Bawahhab; Abdulrahman Yaser Flemban; Amal Ali Dhaifullah Al-Zahrani (Heliyon, 2023)
Background: Mobile phones have become part of everyday life with a potential risk for microbial transmission. Makkah is a mass gathering city that may act as hotspots of disease transmission. The contact between public and both visitors and pilgrims to Makkah can't be overlooked, and any small outbreak within the public can be transmitted rapidly to them. Aim: We aimed to assess knowledge, attitudes, and practices (KAP) of general population towards infection transmission via mobile phones in Makkah and different characteristics relevant to KAP scores. Methods: A cross-sectional web-based survey was conducted on general population in Makkah city using a snowballing sampling method. Participants answered questions about their KAP towards infection transmission via mobile phone. The overall KAP scores were graded as good, fair, and poor and explored against different population characteristics using suitable statistical methods. Results: The study included 385 participants aged 15–64 years. About 88.8% owned personal mobile phone, 3.9% encountering a patient with infections transmitted via mobile phones, and 60.5% know nothing about potential role of mobile phones in infection transmission. Only 16.6% had good knowledge, 64.1% with positive attitudes, and 55.3% reported poor practices. The mean knowledge score was significantly higher among young adults (p = 0.002) and those with higher education (p = 0.005). Their mean attitude and practice scores were significantly higher among older adults (p < 0.001 and p = 0.015), female (p = 0.001 and p = 0.022), and those with higher education (p = 0.036 and p = 0.041) respectively. Conclusion: The overall public knowledge and practices towards the role of mobile phones in infection transmission in Makkah was below average though they have positive attitudes. Raising public awareness is important to decrease the possibility of cross-contamination via mobile phones and to develop adequate preventive strategies in a mass gathering setting like Makkah city.